Experiment of Using Structured Techniques in Intelligence Analysis - Jozef Vojtek (Vojenské rozhledy, 2019)
Research into the use of structured analytical techniques has shown that analysts use specific structured techniques to achieve better analysis results than using traditional intuitive approaches. The experiment was based on solving the analytical tasks of two intelligence scenarios in a set of 32 people. To verify the null hypothesis, a chi-square test of independence was performed at a 5% significance level. In the control/intuitive and experimental/structured technique groups, responses were evaluated in four criteria, in an overall qualitative intelligence analysis, in rank corps, depending on the time of service and education. The number of correct answers was the highest in the experimental group when dealing with the intelligence analysis criteria for both scenarios. Improved analysis of the experimental group in the second scenario solution was statistically significant. The null hypothesis, using structured methodology improves qualitative intelligence analysis, is not rejected. In the experiment, other test criteria are below than the critical value. The results of the research have shown that the success of the problem solution is influenced by the correct use of the Hypothesis Testing technique. The use of structured techniques depends on the level of knowledge and the type of intelligence problem. At the same time, the conduct of research has shown the influence of analysts' cognitive biases